Evaluation of life quality and sleep problems in children presenting with headache to the pediatric neurology outpatient clinic - Ozdemir, Fatih Mehmet Akif; Celik, Halil (EXPERIMENTAL BIOMEDICAL RESEARCH, 2023)
Aim: We aimed to investigate the quality of life (QL) and sleep habits (SH) of children presenting to the pediatric neurology outpatient clinic with headache. Methods: This prospective, cross-sectional and observational survey study included children aged 2-18 who presented to the pediatric neurology outpatient clinics of Dr. Ali Kemal Belviranlı Maternity and Children's Hospital or Konya City Hospital between April and August 2022. QL was assessed using the Pediatric Quality of Life Inventory (PedsQL) and sleep characteristics were evaluated using the Children’s Sleep Habits Questionnaire. Results: The study included 137 patients (56.2% girls) with a mean age of 153.54±34.5 months at presentation. All patients were diagnosed with primary headache; 51.8% had migraine and 48.2% had tension-type headache. Quality of life scores were 69.07±14.96 according to child self-assessment and 66.39±15.37 according to parental assessment. The mean score on the sleep habits questionnaire was 48.01±7.68, and 9.5% of the patients had good sleep quality. Subscale scores showed that the greatest adverse effects on QL were in the areas of emotional functioning and school functioning. Conclusions: Clinical assessment of patients’ QL and SH is important for individualizing treatment and approach in pediatric primary headache.